From phenomenography to variation theory : a review of the development of the variation theory of learning and implications for pedagogical design in higher education. - Akerlind, Gerlese (HERDSA Review of Higher Education v.2 p.5-26, 2015)
The Variation Theory of Learning is a recent development arising out of the phenomenographic research approach. Phenomenography developed in the 1970s as a specialised field of enquiry focused on mapping experiential descriptions of the different ways in which people can understand the same phenomena. These theoretical developments also underpin Variation Theory, and formed the jumping off point for what became a new research direction, towards applied studies of pedagogical applications of the theory to the teaching and learning of disciplinary concepts. This paper reviews the development and application of Variation Theory, and describes the potential of Variation Theory to inform pedagogical design in higher education, using the example of students' learning of the concept of 'legal reasoning' in law to illustrate the type of research processes and outcomes that result from each stage of development of Variation Theory and its pedagogical application. [Author abstract]